2023
DOI: 10.7759/cureus.37916
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Elevated Blood Pressure and Its Association With Obesity in Children Aged 6-13 Years in Rural India: A Cross-Sectional Study

Abstract: IntroductionGlobally, hypertension is one of the major risk factors for cardiovascular disease. Childhood hypertension is one of the emerging conditions due to the increase in the prevalence of obesity in children in developing countries. An increase in blood pressure (BP) can be classified as secondary hypertension if it is caused by an underlying disease process or as primary hypertension if there is no identifiable cause. Primary hypertension during childhood often tracks into adulthood. The prevalence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…11,12 The increasing rates of obesity and overweight among children and adolescents in this region pose substantial challenges to individual health outcomes, healthcare systems, and societal well-being. Research evidence has confirmed the possible causal association of childhood obesity with metabolic syndrome, 13 dyslipidemia, 14 type 2 diabetes mellitus, 15 hypertension, 16 hepatic steatosis, 17 asthma, 18 early onset adulthood cardiovascular diseases, 19 and even premature mortality. 20 According to the World Health Organization (WHO) report, over 1 billion individuals globally are obese (39 million children, 340 million adolescents, and 650 million adults), and these figures are exponentially rising.…”
Section: Introductionmentioning
confidence: 93%
“…11,12 The increasing rates of obesity and overweight among children and adolescents in this region pose substantial challenges to individual health outcomes, healthcare systems, and societal well-being. Research evidence has confirmed the possible causal association of childhood obesity with metabolic syndrome, 13 dyslipidemia, 14 type 2 diabetes mellitus, 15 hypertension, 16 hepatic steatosis, 17 asthma, 18 early onset adulthood cardiovascular diseases, 19 and even premature mortality. 20 According to the World Health Organization (WHO) report, over 1 billion individuals globally are obese (39 million children, 340 million adolescents, and 650 million adults), and these figures are exponentially rising.…”
Section: Introductionmentioning
confidence: 93%